EFFECT OF LENGTH-TO-DIAMETER RATIO ON CRITICAL HEAT FLUX IN POROUS-COATED TUBES - Yildiz, Sebiha (VINCA INST NUCLEAR SCI, 2021)
The critical heat flux occurring during upflow of boiling water in vertical smooth and porous-coated tubes were investigated experimentally. The experiments were performed at low pressures from 0.11-0.7 MPa and at mass fluxes from 100-400 kg/m(2)s, with inlet subcoolings from 1-70 K. The experiments were carried out with four test sections, two of which were porous coated by sintering. The two tubes in each of the cases, porous and smooth, had the same geometries (L/D = 28.3, L/D = 38.75) to ensure a direct comparison of the measured data in the porous-coated tubes with those of the smooth tubes. In addition, the critical heat flux data for water in uniformly heated vertical porous-coated tubes were obtained from the literature. These experiments were conducted using two smooth and four inner porous-coated tubes (L/D = 14.1, L/D = 50) in the same experimental set-up used in the present study. In general, it was found that the critical heat flux decreased with an increase in the L/D ratio for both the smooth and porous-coated tubes. The effect of porous coating on critical heat flux can be positive, negative, or even neutral.
Keywords: L/D ratio; critical heat flux; smooth tube; porous-coated tube; vertical; water; upflow; Thermodynamics